Changes of volatile substance composition during processing of nine-processed tangerine peel (Jiuzhi Chenpi) determined by gas chromatography-ion mobility spectrometry - Fu, Manqin; Wang, Yuehan; Yu, Yuanshan; Wen, Jing; Cheong, Meng Sam; Cheang, Wai San; Wu, Jijun (Frontiers in Nutrition, 2022)
Nine-processed tangerine peel (Jiuzhi Chenpi in Chinese) is a famous Chinese traditional snack. The composition and contents of volatile substances during its processing is unclear. Gas chromatography combined with ion mobility spectrometry (GC-IMS) was applied to determine the characteristic changes of volatile components throughout the production process. Four stages such as untreated dry tangerine peel (raw material), debittered tangerine peel, pickled tangerine peel, and final product were examined. A total of 110 flavor compounds were successfully detected in tangerine peel samples across the various production stages. The final product contained low amount of terpenes, esters and alcohols, which were lost during processing; while the final product contained increased amount of aldehydes and very high level of acetic acid. Present findings help to understand the formation of the unique flavor of nine-processed tangerine peel and provide a scientific basis for the optimization of processing methods and quality control.